Meiofauna in the organic shrimp farms of mangrove forest, Ca Mau province - Thai, Tran Thanh; My Yen, Nguyen Thi; Tho, Nguyen; Quang, Ngo Xuan (Vietnam Journal of Science and Technology, 2017)
Meiofaunal communities in the mangrove – shrimp farms system (MSFS) of Ca Mau province was investigated in 8 ponds (Tam Giang Commune, Nam Can District). Results showed that the meiofauna, especially nematodes at the Tam Giang’s MSFS in Ca Mau mangrove express high densities and biodiversity and nematodes dominate numerically in the mangrove meiofauna (73.69 to 96.2 %). In total, 15 major taxa were found with the dominant taxa belonged to three dominant groups: Nematodes, Copepoda, and Rotifera. The densities of meiofauna ranged from 287 ± 132.9  to 3129 ± 1388.6 inds.10 cm-2. Seventy fifth nematode genera belonging to 24 families with the most important typifying genera were Terschellingia, Daptonema, Parodontophora, Ptycholaimellus, Sabatieria, Hopperia, Anoplostoma, Pseudolella, Gomphionema. The mangrove – shrimp farms system in the study area was characterized by homogeneity and stabilization.